Assembling governance in São Paulo's "Cracolândia" - Richmond, Matthew A.; Magri, Giordano (Political geography, 2025)
This article explores current governance arrangements in “Cracolândia” (“Crackland”), a heterogeneous area in central São Paulo where large numbers of crack cocaine users occupy public spaces. The territory has long been subject to public interventions in the fields of security, social assistance, health and housing, but is also shaped by the activities of an array of nonstate governance actors, including community associations, NGOs, and organised crime. We present four ethnographic case studies of women who vary markedly in terms of their social characteristics, living conditions, and relationships to the territory to explore the diverse ways that they define and seek to address governance problems. We find that each uses the resources and relationships available to them to individually “assemble governance”, by developing problem-solving strategies and interacting with different combinations of state and nonstate actors. However, these contrasting cases also shed light on broader governance arrangements. They reveal how, even in the context of normative ruptures and everyday tensions, a range of situated and provisional mechanisms of mutual accommodation partially integrate distinct governance actors into a broader territorial governance assemblage.